p14(ARF) Genetic Polymorphisms and Susceptibility to Second Primary Malignancy in Patients with Index Squamous Cell Carcinoma of the Head and Neck - Zhang, Yang (2010)
BACKGROUND: p14(ARF) plays a critical role in crosstalk between p53 and Rb pathways and in cellular anticancer mechanisms. We, therefore, investigated the association between the single nucleotide polymorphisms (SNPs) of p14(ARF) and risk of second primary Malignancy (SPM) after index squamous cell carcinoma of the head and neck (SCCHN). METHODS: We used Log-rank test and Cox proportional hazards models to assess the association of the two p14(ARF) SNPs (rs3731217 and rs3088440) with the SPM-free survival and SPM risk among 1,287 incident SCCHN patients. RESULTS: We found that patients with either p14(ARF) variant genotypes of the two polymorphisms had a significantly reduced SPM-free survival, compared with patients with no variant genotypes (Log-rank test, P = 0.006). Compared with p14(ARF) TT and GG genotypes, the variant genotypes of p14(ARF) TG/GG and GA/AA were associated with significantly moderately increased risk of developing SPM [adjusted hazard ratio (aHR), 1.48, 95% confidence interval (CI), 1.00–2.19 for p14(ARF)-rs3731217 and aHR, 1.61, 95% CI, 1.07–2.43 for p14(ARF)-rs3088440), respectively]. Moreover, after combining the variant genotypes of the two SNPs, patients with variant genotypes had a significantly greater risk for SPM compared to patients with no variant genotypes (aHR, 3.07, 95% CI, 1.54–6.12), and the risk was particularly pronounced in several subgroups. CONCLUSIONS: Our results suggest a modestly increased risk of SPM after index SCCHN with each p14(ARF) polymorphism and an even greater risk of SPM with combined variant genotypes of the two SNPs. Therefore, p14(ARF) polymorphisms may be a susceptible marker to SPM risk for SCCHN patients.